EFFECT OF OPERATING COSTS AND REVENUES ON FINANCIAL PERFORMANCE BASED ON RETURN ON ASSETS RATIO (ROA) IN PLASTICS AND PACKAGING SUB-SECTOR INDUSTRIAL COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Sahri Maulana Hadi; Tabita Nawarisa Tarigan; Reka Marito Br Siregar; Lidia Liski Purba; Oki Prayogi (SEAN Institute, 2023)
The purpose of study was to determine the effect of operating costs and income on financial performance based on the ratio of Return On Assets (ROA) in plastic and packaging sub-sector industrial companies listed on the Indonesia Stock Exchange.The research method used is quantitative research. The population used is all plastic and packaging sub-sector companies listed on the Indonesia Stock Exchange (IDX) for 2019-2021 totaling 13 companies. The sample that passed based on category was 6 companies. The data analysis technique used is multiple linear regression analysis. The results showed that operational costs had a significant value of 0,000 > 0,05 so that it was concluded that operational cocts had an influence on financial performance based on the Return On Assets ratio in plastic and packaging sub-sector industrial companies listed on the Indonesia StockExchange.